THE PECULIARITY OF GENE EXPRESSION IN TOXIC LIVER DAMAGE WITH ACRYLAMIDE - Якупова, Татьяна Георгиевна; Каримов, Денис Олегович; Хуснутдинова, Надежда Юрьевна; Репина, Эльвира Фаридовна; Валова, Яна Валерьевна; Мухаммадиева, Гузель Фанисовна (Medicine in Kuzbass, 2023)
The purpose of the study – to study the features of the expression of oxidative stress genes under prolonged exposure to acrylamide. Materials and methods. The studies were performed on white outbred female rats with an initial body weight of 190-192 g. For the purpose of preventive correction, solutions of compounds were administered intragastrically to animals 1 hour before the toxicant: MG-1 and MG-2 – 0.5 % aqueous solution at a dose of 50 mg/kg body weight; MG-10 – 5 % aqueous solution at a dose of 500 mg/kg of body weight. A 0.2 % aqueous solution of acrylamide was used as a toxicant. cDNA synthesis was performed from a matrix of isolated total RNA. The study of gene expression in normal and during acrylamide intoxication was carried out by real-time PCR. Results. The CASP7 gene showed statistically significant differences (k = 10.07; p = 0.039). The minimum value of this gene was -0.46 [-1.49; 2.06] in the intact group, and the maximum value was 3.87 [2.26; 8.32] in the MG-10 group. The expression level of the CHEK gene (k = 12.73; p = 0.013) reached its maximum value in the group of preventive correction MG-10 (4 [-0,07; 8,49]), and the minimum is in the MG group-2 (-0,8 [-0,96; -0,33]). The minimum value of the RIPK gene was -0.18 [-0.57; 0.69] in the negative control group, and the maximum value was 3.46 [2.02; 6.33] in the MG-10 group. Statistical significance was achieved when comparing the negative and positive control groups with the MG-2 and MG-10 groups. Conclusion. The effect of acrylamide increases the expression of the main detoxification genes in the liver tissue and protects the cell from damage. Acrylamide at a dose of 20 mg/kg of animal body weight in a subacute experiment has a mild toxic effect on the body, expressed in a change in genetic parameters.